Obstacles, research progress, and prospects of oral delivery of bioactive peptides: a comprehensive review - Wang, Xinyu; Yang, Zeyao; Zhang, Wangang; Xing, Lujuan; Luo, Ruiming; Cao, Songmin (Frontiers in Nutrition, 2024)
Bioactive peptides hold significant potential for enhancing human health, however, their limited oral bioavailability poses a substantial barrier to their widespread use in the food and pharmaceutical industries. This article reviews the key factors influencing the absorption efficiency of oral bioactive peptides, including issues related to bitter taste perception, challenges in gastrointestinal environmental stability, and limitations in transmembrane transport. Furthermore, it highlights the latest technologies, such as osmotic technology, chemical modification, and advanced delivery systems, and discusses their advantages in enhancing the stability of bioactive peptides and facilitating intestinal absorption. In addition, the application and challenges of common delivery systems such as liposomes, emulsions, polymer nanoparticles, and hydrogels in oral bioactive peptide delivery are also discussed. This paper aims to provide a theoretical foundation for scientific research and practical applications of oral delivery of bioactive peptides, thereby promoting the further development of bioactive peptides in the context of human health.